POLA ASUH IBU TUNGGAL DALAM MENGEMBANGKAN KECERDASAN SOSIAL ANAK USIA DINI (Studi Deskriptif pada Anak Usia 4 - 6 Tahun) - Rizka Fadliah Nur (Pusat Studi Gender dan Anak, IAIN Palu, 2021)
The purpose of this study was to determine the role of mothers as single parents in developing their children's intelligence at the age of 4-6 years. This study uses a descriptive quantitative approach with a single variable, namely social intelligence. Social intelligence consists of aspects of social sensitivity, social insight, and social communication. This aspect of social intelligence must be possessed by early childhood. Social intelligence includes empathy, prosocial, self-awareness, understanding of social situations and social ethics, problem solving skills, effective communication, effective listening and being able to lead groups. These skills can be taught to children starting from an early age by their parents, mothers who act as single parents have their own ways to help their children's development because social intelligence in early childhood is not naturally possessed by children, but must be grown and developed. by parents by developing the social and emotional aspects of early childhood. That is why we need various methods that can be used to develop it. One method that parents can use in developing social and emotional aspects in early childhood is through example. Exemplary activities that can be done to develop emotional social intelligence in early childhood.